UNSUR-UNSUR DELIK MATERIEL DAN DELIK FORMIL DALAM HUKUM PIDANA LINGKUNGAN - Indah Sari (JURNAL ILMIAH HUKUM DIRGANTARA, 2019)
Abstract :This writing is generally about Environmental Criminal Law which consists of criminal aspects of environmental law. Enviromental Protection and Governance Act No. 32 Year 2009 article 97 to article 120 regulate about this environmental crime. It stated there that environmental crime is a forbidden deed considered as a deed against the law for it cause an enviromental damage by polluting and contaminating environment.  There are material and formal criminal act in this environmental criminal act; a material act consider the effect of those criminal deeds, while a formal act focus more on the illegal action. This paper analyze both material and formal criminal act as regulated in Enviromental Protection and Governance Act No. 32 Year 2009, specifically at articles 98, 99 and 112 for the material act, while for formal act covered by articles 100-111 and articles 113-115. Keywords: Environmental Criminal Law, Environmental Crime, Material Criminal Act, Formal Criminal Act, Enviromental Protection and Governance Act No.32 Year 2009